Src: Marker or Actor in Prostate Cancer Aggressiveness - Vlaeminck-Guillem, Virginie; Gillet, Germain; Rimokh, Ruth (Frontiers in Oncology, 2014)
A key question for urologic practitioners is whether an apparently organ-confined prostate cancer (PCa) is actually aggressive or not. The dilemma is to specifically identify among all prostate tumors the very aggressive high-grade cancers that will become life-threatening by developing extra-prostatic invasion and metastatic potential and the indolent cancers that will never modify a patient’s life expectancy. A choice must be made between several therapeutic options to achieve the optimal personalized management of the disease that causes as little harm as possible to patients. Reliable clinical, biological, or pathological markers that would enable distinctions to be made between aggressive and indolent PCas in routine practice at the time of initial diagnosis are still lacking. The molecular mechanisms that explain why a PCa is aggressive or not are also poorly understood. Among the potential markers and/or actors in PCa aggressiveness, Src and other members of the Src kinase family, are valuable candidates. Activation of Src-dependent intracellular pathways is frequently observed in PCa. Indeed, Src is at the cross-roads of several pathways [including androgen receptor (AR), TGFbeta, Bcl-2, Akt/PTEN or MAPK, and ERK …], and is now known to influence some of the cellular and tissular events that accompany tumor progression: cell proliferation, cell motility, invasion, epithelial-to-mesenchymal transition, resistance to apoptosis, angiogenesis, neuroendocrine differentiation, and metastatic spread. Recent work even suggests that Src could also play a part in PCa initiation in coordination with the AR. The aim of this review is to gather data that explore the links between the Src kinase family and PCa progression and aggressiveness.